Associations of per- and polyfluoroalkyl substances in follicular fluid with polycystic ovarian syndrome in infertile women may be mediated by sex hormones - Bian, Yating; Yue, Yingxiao; Cheng, Yufan; Wang, Dan; He, Lu; Yan, Peixia; Song, Huan; Wang, Tong; Zhou, Weidong; Zhang, Xu; Pan, Zhizhen; Liu, Liangpo (Frontiers in Public Health, 2025)
ObjectivesPer- and polyfluoroalkyl substances (PFAS) have been associated with polycystic ovarian syndrome (PCOS), however, the evidence is limited. This study aimed to explore the associations between PFAS in the follicular fluid and PCOS, as well as the mediating role of steroid hormones.MethodsForty women with PCOS undergoing treatment for infertility and 56 control participants were included in this study. The levels of 24 PFAS in the follicular fluid and sex hormones in serum were measured. The adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for each PFAS were estimated by multivariable logistic regression. Correlation analysis and multiple linear regression revealed the associations between PFAS and steroid hormones. Bayesian kernel machine regression (BKMR) model was utilized to evaluate the associations between joint and individual PFAS exposure and PCOS. Additionally, in-vitro experiment with human ovarian granulosa cell line (KGN cells) was conducted.ResultsThe study showed that perfluoro-n-octanoic acid (PFOA) and potassium perfluoro-1-octanesulfonate (PFOS) were the dominant PFAS in the follicular fluid samples, with the median concentration of 4.35 ng/mL and 5.22 ng/mL, respectively. Perfluoro-n-hexanoic acid (PFHxA) were correlated with increased incidences of PCOS (medium vs. low tertile: OR = 1.78, 95% CI: 0.18, 17.19). In the cases, a negative relationship was found between PFHxA and luteinizing hormone (LH; β = −0.44, 95% CI: −8.25, −0.03), while a positive relationship was observed between perfluoro-n-heptanoic acid (PFHpA) and LH (β = 0.504, 95% CI: 0.71, 21.31). PFOA was positively associated with estradiol (E2; β = 0.76, 95% CI: 1.52, 19.57). The BKMR model indicated that there might be a joint effect between PFAS mixtures and PCOS, with the posterior inclusion probabilities (PIP) of PFHxA was 0.983. In the cell experiments, PFOA, PFOS, and PFHpA exposure decreased the concentration of E2 (p < 0.05).ConclusionPFHxA in follicular fluids was associated with the elevated odds of PCOS, and steroid hormones may play a role in the etiologic connection.